PERSEPSI SISWA TERHADAP PENGGUNAAN GOOGLE CLASSROOM DALAM PEMBELAJARAN AKUNTANSI DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Aylincia Excelina Yofeigo; Tiara Tiara; Sri Kantun (Universitas Muhammadiyah Surakarta, 2022)
The Covid-19 pandemic since April 2020 in accordance with the Decree of the Minister of Education and Culture of Indonesia No. 4 of 2020 caused a paradigm shift in learning activities from conventional to online systems. SMKN 1 Jember is one of the schools that implement the system, especially in accounting subjects. This study aims to determine the perception of class X Accounting students on the use of Google Classroom in online accounting learning with the Technology Acceptance Model (TAM) approach. This type of research uses explanatory research with a quantitative approach. Data collection methods used are questionnaires, interviews, documents and observations. The data analysis method uses Structural Equation Modeling (SEM) with SmartPLS version 3.3.2 data measurement. The results showed that H1: perceived ease of use on perceptions of usefulness in the use of Google Classroom had a significant effect of 69.5%, H2: perceived usefulness on attitudes to using Google Classroom had a significant effect of 88.8%, H3: perceived ease of use on Attitude to use Google Classroom has no significant effect at 7%, H4: Attitude to use Google Classroom has a significant effect at 71.7% and H5: intention to use Google Classroom has a significant effect at 84.2%. Of all the hypothesis testing has a significant effect. However, there is one hypothesis that does not provide usefulness and benefits in its use, then H3 shows a negative result. Therefore, further research is needed regarding the perception of ease of use on usage attitudes in the use of Google Classroom.